2014
DOI: 10.5127/jep.038113
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Control and Rumination in Youth: The Importance of Emotion

Abstract: Rumination involves the tendency to passively dwell on negative emotions along with their meanings and consequences. Susan Nolen–Hoeksema demonstrated the role of rumination in the development of several forms of psychopathology and suggested that cognitive control may be one factor that makes some individuals more prone to ruminate than others. Studies with adults have consistently found that rumination is associated with cognitive control difficulties, especially related to switching and inhibiting emotional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 45 publications
(76 reference statements)
3
30
0
Order By: Relevance
“…In addition, because we used a single task to assess attention, we cannot be sure whether attentional patterns among youth who ruminate are specific to emotional or more general stimuli. However, in another study of youth, rumination was associated with attentional patterns on an affective task but not a general cognitive task (Hilt et al, 2014). It will be important for future research to examine additional tasks with varying stimuli to better understand the extent of attentional patterns among youth who ruminate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, because we used a single task to assess attention, we cannot be sure whether attentional patterns among youth who ruminate are specific to emotional or more general stimuli. However, in another study of youth, rumination was associated with attentional patterns on an affective task but not a general cognitive task (Hilt et al, 2014). It will be important for future research to examine additional tasks with varying stimuli to better understand the extent of attentional patterns among youth who ruminate.…”
Section: Discussionmentioning
confidence: 99%
“…Second, this study extends research on the association between selective attention and rumination to a younger sample than has previously been examined. Now that a preliminary body of evidence suggests that attentional control difficulties are associated with rumination by early adolescence (also see Hilt et al, 2014; Romens & Pollak, 2012), we can examine the development of attentional control and rumination prospectively with younger samples to help understand the temporal relationships between these two processes. In addition, because rumination is associated with the development of psychopathology by adolescence (e.g., Rood et al, 2009), a greater understanding of this correlate could offer an avenue for prevention in the form of attention training.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10,[18][19][20][21][22][23] Aberrant attentional shifting may result in excessive internally oriented attention that results in failure to use external stimuli to disengage from rumination, rendering them inflexible to changes in environmental context. [10,23] Studies have demonstrated an inverse association between attentional shifting and rumination, [24] particularly in the context of negative emotional information, [18,25] although this association is less consistent among adolescents, with some studies finding no associations between attentional shifting for neutral stimuli and rumination. [20,26] Although it is plau-sible that deficits in attentional shifting and rumination are correlated, attentional shifting and rumination also could work synergistically such that rumination may be particularly likely to lead to depression among individuals who have difficulty switching attention away from ruminative processes.…”
Section: Introductionmentioning
confidence: 99%
“…Emotions are an essential component of mental life and adaptive behaviors, with profound impact on our perception, memories, actions, and thoughts. In particular, negative affect may impair the efficiency of high-level cognitive processes and reduce cognitive control (Hilt et al 2014). Further, experiencing negative emotions has been associated with cognitive inflexibility (Davis and Nolen-Hoeksema 2000) and difficulties in mental switching (Piguet et al 2010(Piguet et al , 2016.…”
Section: Introductionmentioning
confidence: 99%